CLINICIAN’S VIEW ON THE IMPORTANCE OF RADIOLOGY REPORT IN THEIR DAILY PRACTICE - Astawa, Gregorius Adista Enrico; Meilani, Yohana F. Cahya Palupi (JURNAL WIDYA MEDIKA, 2022)
Bacground: A radiology report is a medicolegal document and formal communication between a radiology radiologist and referring physician/clinician. The failure of radiologists to communicate good quality reports often occurs in the process of patient diagnosis. This study aims to determine the clinician’s view on the importance of radiology reports in patient management of their daily practice in Papua and West Papua. Method: One hundred and eighty-four general practitioners and internship doctors answered an online questionnaire distributed randomly. Forty-five indicators assessed the accessibility to radiology reports, the importance of radiology reports, attached clinical information, clinician satisfaction, structure, and content of radiology reports. This study has seven variables with six paths tested using the Structural Equation Modeling (PLS-SEM) analysis method based on Partial Least Squares based using SmartPLS. Result: Data analysis showed that radiology reports, clinical information, clinician satisfaction, and structure of radiology reports had a positive and significant effect on patient management, while accessibility and content of radiology reports had no significant effect on patient management. Conclusion: Clinicians thought the radiology report was an important medical document that has a role in patient management of their daily practice.